Analisis Hukum Pidana Internasional Terkait Konflik Kemanusiaan Di Timor Timur oleh Pengadilan Dili - Abraham Ethan Martupa Sahat Marune (Jurnal Syntax Transformation, 2021)
The Dili Court is the venue for processing international criminal cases regarding the humanitarian conflict in the tragedy of Timor Leste or East Timor in 1999, which was initiated by the issue of the Indonesian state border with the territory of East Timor which became the main trigger of political aggregates and military aggression which involved many of the indigenous people of East Timor. who are victims. In this study, the author will discuss the analysis of international criminal law related to the humanitarian conflict in East Timor by the Dili court. This research uses normative and qualitative juridical research methods. In this research, the author discusses the history of the establishment of the Dili Court, legal analysis related to the international criminal settlement scheme by the Dili court, as well as the difficulties and obstacles faced by the Dili court to process serious crimes in 1999. Based on the research, the author concludes that law enforcement in serious crimes In Dili, it is considered very difficult to enforce because of the inequality of exclusive authority from both parties, on the one hand, the existence of East Timor which is still politically and economically dependent on the Indonesian state, resulting in this criminal lawsuit to a dead end. On the other hand, the granting of authority is misused for personal interests, which in a militant scheme, the Indonesian military may have been used as an instrument by certain elite figures which resulted in violent upheaval and massacres could occur